The aryl hydrocarbon receptor links integrin signaling to the TGF-β pathway - Silginer, Manuela; Bunse, Lukas (Oncogene, 2016)
Glioblastoma is the most common and aggressive form of intrinsic brain tumor. Transforming growth factor (TGF)-β represents a central mediator of the malignant phenotype of these tumors by promoting invasiveness and angiogenesis, maintaining tumor cell stemness and inducing profound immunosuppression. Integrins, which are highly expressed in glioma cells, interact with the TGF-β pathway. Furthermore, a link has been described between activity of the transcription factor aryl hydrocarbon receptor (AhR) and TGF-β expression. Here we demonstrate that integrin inhibition, using αv, β3 or β5 neutralizing antibodies, RNA interference-mediated integrin gene silencing or pharmacological inhibition by the cyclic RGD peptide EMD 121974 (cilengitide) or the non-peptidic molecule GLPG0187, inhibits AhR activity. These effects are independent of cell detachment or cell density. While AhR mRNA expression was not affected by integrin inhibition, AhR total and nuclear protein levels were reduced, suggesting that integrin inhibition-mediated regulation of AhR may occur at a post-transcriptional level. AhR-null astrocytes, AhR-null hepatocytes or glioblastoma cells with a transiently silenced AhR gene showed reduced sensitivity to integrin inhibition-mediated alterations in TGF-β signaling, indicating that AhR mediates integrin control of the TGF-β pathway. Accordingly, there was a significant correlation of αv integrin levels with nuclear AhR and pSmad2 levels as determined by immunohistochemistry in human glioblastoma in vivo. In summary, this study identifies a signaling network comprising integrins, AhR and TGF-β and validates integrin inhibition as a promising strategy not only to inhibit angiogenesis, but also to block AhR- and TGF-β-controlled features of malignancy in human glioblastoma.